Pengaruh Kepemimpinan Kepala Sekolah Terhadap Motivasi Kerja Tenaga Administrasi di SD Inpres 3 Talise Kota Palu - Niftahuljannah Imran; Naima; Yulia (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2026)
The purpose of this study was to determine the effect of principal leadership on the work motivation of administrative staff at SD Inpres 3 Talise, Palu City. This study used a quantitative method with a descriptive approach. The study population consisted of 6 administrative staff, so the entire population was sampled using a saturated sampling technique. In this study, the data collection method was carried out through a questionnaire using a Likert scale. Data analysis used validity, reliability, normality, and simple linear regression tests with the help of SPSS. The results showed that principal leadership had a positive and significant effect on the work motivation of administrative staff. This was evidenced by a significance value smaller than 0.05 so that the research hypothesis was accepted. The better the principal's leadership, the higher the work motivation of administrative staff. This study recommends that principals improve their leadership, communication, supervision, and motivational skills to administrative staff so that their performance and work spirit are optimal.